8.2k views
1 vote
G(x) = 15 - 4x

3
h(x) = x+8
Write g(h(x)) as an expression in terms of x.
g(h(x)) =

G(x) = 15 - 4x 3 h(x) = x+8 Write g(h(x)) as an expression in terms of x. g(h(x)) =-example-1
User Greenhouse
by
5.0k points

1 Answer

4 votes

Answer:


g(h(x))=−6x−17</p><p>

Explanation:

given:


g(x) = 15 - 4x \\ h(x) = (3)/(2 ) x + 8

To find g(h(x)) substitute h(x) instead of every x in g(x)

therefore:


g(h(x)) = 15 - 4( (3)/(2) x + 8) \\

simplify


g(h(x)) = 15 - 6x - 32 \\ g(h(x)) = - 6x - 17

User David Maze
by
4.2k points